2021
DOI: 10.1111/aor.13918
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative prothrombin complex concentrate administration and outcomes in patients undergoing left ventricular assist device implantation

Abstract: Prothrombin complex concentrate (PCC) administration has increased among cardiac surgery patients in recent years; however, use in LVAD implantation/exchange is not widespread due to the fear of thrombotic complications. The purpose of this study was to compare the clinical outcomes of patients undergoing LVAD implantation/exchange with intraoperative PCC administration versus traditional transfusion practices alone. Adult LVAD implants/exchanges at our institution between 2015 and 2018 were included. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…Bleeding and right ventricular dysfunction are associated with morbidity and mortality in patients undergoing LVAD implantation 9,10,14 . Management strategies designed to limit volume overload and reduce right ventricular dysfunction, such as the use of prothrombin complex concentrates, have been described, though concerns regarding safety have limited widespread adoption 15 . An alternative transfusion technique unique to cardiac surgery is the administration of plasma late on CPB, which theoretically allows for the augmentation of factor levels while preserving the ability to remove excess volume via ultrafiltration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bleeding and right ventricular dysfunction are associated with morbidity and mortality in patients undergoing LVAD implantation 9,10,14 . Management strategies designed to limit volume overload and reduce right ventricular dysfunction, such as the use of prothrombin complex concentrates, have been described, though concerns regarding safety have limited widespread adoption 15 . An alternative transfusion technique unique to cardiac surgery is the administration of plasma late on CPB, which theoretically allows for the augmentation of factor levels while preserving the ability to remove excess volume via ultrafiltration.…”
Section: Discussionmentioning
confidence: 99%
“…been described, though concerns regarding safety have limited widespread adoption. 15 An alternative transfusion technique unique to cardiac surgery is the administration of plasma late on CPB, which theoretically allows for the augmentation of factor levels while preserving the ability to remove excess volume via ultrafiltration. The purpose of this study was to compare perioperative outcomes for patients undergoing LVAD implantation receiving plasma late on CPB to similar patients who did not receive plasma on bypass.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there was a nonsignificant trend toward higher LVAD pump thrombosis with PCC (2.6% v 0.8%, p = 0.98). 33 In another retrospective investigation of activated PCC (factor VIII inhibitor bypassing activity [FEIBA]) for post-LVAD coagulopathy, FEIBA use was associated with no increase in 14-day thrombotic outcomes (11.0% v 7.6%, p = 0.343) or mortality rate (3.7% v 1.3%, p = 0.179). 34 Although the authors suggested a favorable risk-benefit profile for FEIBA use in LVAD surgery, they acknowledged that future studies still are required to fully assess the safety profile.…”
Section: Prothrombin Complex Concentratesmentioning
confidence: 99%
“…Distinct advantages to PCC administration include higher factor concentration with significantly less infusate volume, ambient storage (ie, at room temperature) with rapid reconstitution, not having to worry about ABO blood group compatibility, and lower risk of transfusion-related complications . To our knowledge, data evaluating the use of PCCs in this population are limited to retrospective studies and 2 prospective pilot studies, which have demonstrated faster return of the international normalized ratio (INR) to the target range, reduced blood loss and transfusion requirements, more effective hemostasis, and an adverse event rate similar to that of plasma transfusion …”
Section: Introductionmentioning
confidence: 99%
“…5 To our knowledge, data evaluating the use of PCCs in this population are limited to retrospective studies and 2 prospective pilot studies, which have demonstrated faster return of the international normalized ratio (INR) to the target range, reduced blood loss and transfusion requirements, more effective hemostasis, and an adverse event rate similar to that of plasma transfusion. 3,[6][7][8][9][10][11][12][13][14][15] The purpose of this study was to analyze perioperative outcomes in patients undergoing CPB surgery, with particular fo-cus on bleeding, transfusion, and thrombotic complications. We hypothesized that PCC use would reduce bleeding and transfusion requirements in cardiac surgical patients without increasing thrombotic complications.…”
mentioning
confidence: 99%